2021
DOI: 10.1039/d1cp03832j
|View full text |Cite
|
Sign up to set email alerts
|

Mixed fatty acid-phospholipid protocell networks

Abstract: This study shows the autonomous transformation of fatty acid-containing lipid reservoirs to model protocell networks on solid substrates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, this model suffers that ingredients can enter and exit droplets freely, and one prefers a protocell recipient that is made of a lumen that can indeed encapsulate ingredients but is also closed by a lipid bilayer. [30,[49][50][51][52][53][54][55][56][57] Interestingly, recent works have shown that vesicles can be produced from double (water-in-oilin-water droplets) emulsions. [58][59][60][61][62][63] These were prepared by microfluidics and this allows encapsulating cargoes in their lumen.…”
Section: Introductionmentioning
confidence: 99%
“…However, this model suffers that ingredients can enter and exit droplets freely, and one prefers a protocell recipient that is made of a lumen that can indeed encapsulate ingredients but is also closed by a lipid bilayer. [30,[49][50][51][52][53][54][55][56][57] Interestingly, recent works have shown that vesicles can be produced from double (water-in-oilin-water droplets) emulsions. [58][59][60][61][62][63] These were prepared by microfluidics and this allows encapsulating cargoes in their lumen.…”
Section: Introductionmentioning
confidence: 99%
“…21 Membranes composed of unsaturated lipids are revealed to exhibit enantioselective permeability to sugars, simple carbohydrates, 22 and dipeptides. 23 Modulating the physical properties of the membrane by lipids made of unsaturated chains, 23 short chain length lipids, 24 branched lipids, 25 and single chain amphiphiles 26,27 can also impart permeability to vesicles.…”
mentioning
confidence: 99%